STRATEGI PEMASARAN USAHA SAYURAN HIDROPONIK DI IJAL FARM TULUNGAGUNG - Herry Nur Faisal (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2024)
This study aims to determine income, marketing channels, and determine hydroponic marketing strategies at Ijal Farm, Tulungagung Regency. This study uses a descriptive qualitative analysis method using SWOT analysis. The results of the study indicate that the position of the Ijal Farm farming business is in quadrant 1, which means that the strength of Ijal Farm, Tulungagung Regency in marketing hydroponic vegetables is greater than its weaknesses and there are more opportunities than threats. The recommended strategy is an aggressive strategy, meaning utilizing the strengths and capabilities of Ijal Farm to overcome existing weaknesses and threats. The marketing strategy used is to sell directly to customers who have been recorded or around residential areas or greenhouses, increase promotions to minimarkets, supermarkets and frozen markets in Tulungagung Regency and conduct promotions through social media to expand the promotional network